A Comparison of Red Cell Rejuvenation versus Mechanical Washing for the Prevention of Transfusion-associated Organ Injury in Swine. (February 2018) - Woźniak, Marcin J.; Qureshi, Saqib; Sullo, Nikol; Dott, William; Cardigan, Rebecca; Wiltshire, Michael; Nath, Mintu; Patel, Nishith N.; Kumar, Tracy; Goodall, Alison H.; Murphy, Gavin J.
Abstract : Background: We evaluated the effects of two interventions that modify the red cell storage lesion on kidney and lung injury in experimental models of transfusion. Methods: White–landrace pigs (n = 32) were allocated to receive sham transfusion (crystalloid), 14-day stored allogeneic red cells, 14-day red cells washed using the red cells washing/salvage system (CATS; Fresenius, Germany), or 14-day red cells rejuvenated using the inosine solution (Rejuvesol solution; Zimmer Biomet, USA) and washed using the CATS device. Functional, biochemical, and histologic markers of organ injury were assessed for up to 24 h posttransfusion. Results: Transfusion of 14 day red cells resulted in lung injury (lung injury score vs. sham, mean difference −0.3 (95% CI, −0.6 to −0.1; P = 0.02), pulmonary endothelial dysfunction, and tissue leukocyte sequestration. Mechanical washing reduced red cell–derived microvesicles but increased cell-free hemoglobin in 14-day red cell units. Transfusion of washed red cells reduced leukocyte sequestration but did not reduce the lung injury score (mean difference −0.2; 95% CI, −0.5 to 0.1; P = 0.19) relative to 14-day cells. Transfusion of washed red cells also increased endothelial activation and kidney injury. Rejuvenation restored adenosine triphosphate to that of fresh red cells and reduced microvesicle concentrations without increasing cell-free hemoglobin release. Transfusion of rejuvenated red cells reduced plasma cell-free hemoglobin, leukocyte sequestration, and endothelial dysfunction in recipients and reduced lung and kidney injury relative to 14-day or washed 14-day cells. Conclusions: Reversal of the red cell storage lesion by rejuvenation reduces transfusion-associated organ injury in swine. Abstract : In a porcine model, red blood cell washing along with an inosine rejuvenation solution restored red cell energy stores, reduced inflammatory responses, and reduced transfusion-associated organ injury in swine in 14-day-old stored blood.Supplemental Digital Content is available in the text.